Stability of an aluminum salt-adjuvanted protein D-conjugated pneumococcal vaccine after exposure to subzero temperatures - Juliette Fortpied; Florence Wauters; Christelle Rochart; Philippe Hermand; Bernard Hoet; Nicolas Moniotte; Ivo Vojtek (Taylor & Francis Group, 2018)
Accidental exposure of a vaccine containing an aluminum-salt adjuvant to temperatures below 0°C in the cold chain can lead to freeze damage. Our study evaluated the potential for freeze damage in a licensed aluminum-salt-containing protein-D-conjugated pneumococcal vaccine (PHiD-CV; Synflorix, GSK) in conditions that included static storage, single subzero-temperature excursions, and simulated air-freight transportation. Several parameters were assessed including freezing at subzero temperatures, aluminum-salt-particle size, antigen integrity and immunogenicity in the mouse. The suitability of the WHO's shake test for identifying freeze-damaged vaccines was also assessed. During subzero-temperature excursions, the mean temperatures at which PHiD-CV froze (−16.7°C to −18.1°C) appeared unaffected by the type of vaccine container (two-dose or four-dose vial, or single-dose syringe), vaccine batch, rotational agitation, or the rate of temperature decline (−0.5 to −10°C/hour). At constant subzero temperature and in simulated air-freight transportation, the freezing of PHiD-CV appeared to be promoted by vibration. At −5°C, no PHiD-CV sample froze in static storage (>1 month), whereas when subjected to vibration, a minority of samples froze (7/21, 33%) within 18 hours. At −8°C with vibration, nearly all (5/6, 83%) samples froze. In these vibration regimes, the shake test identified most samples that froze (10/12, 93%) except two in the −5°C regime. Nevertheless, PHiD-CV-antigen integrity appeared unaffected by freezing up to −20°C or by vibration. And although aluminum-salt-particle size was increased only by freezing at −20°C, PHiD-CV immunogenicity appeared only marginally affected by freezing at −20°C. Therefore, our study supports the use of the shake test to exclude freeze-damaged PHiD-CV in the field.